A CLINICAL CASE OF EXFOLIATING AORTIC ANEURYSM FROM THE PRACTICE OF AN ON-DUTY SURGEON - Павленко, Владимир Вячеславович; Старцев, Андрей Борисович; Слободина, Алена Олеговна; Каменева, Евгения Александровна; Лесников, Степан Михайлович (Medicine in Kuzbass, 2025)
The article describes a clinical case of a delaminating aortic aneurysm from the practice of an on-duty surgeon. Exfoliating aortic aneurysm is a complication of the development of aortic disease and the cause of sudden deaths in 3-4% of cases [1, 2]. Aortic dissection (RA) is the formation of a defect (rupture) of the inner lining of the aortic wall, followed by blood flow into the degeneratively altered middle layer. RA is an urgent condition that can lead to death. Mortality due to aortic rupture is 80%, and half of the patients die after being admitted to the hospital. If the dissection reaches 6 cm or more, the patient must undergo urgent surgery. [3]. Timely detection and treatment of RA is crucial to prevent the development of this serious condition.
Keywords: delaminating aortic aneurysm; CT OBP with bolus contrast